Homochiral Self‐Sorted and Emissive IrIII Metallo‐Cryptophanes. Issue 26 (20th April 2017) - Pritchard, Victoria E.; Rota Martir, Diego; Oldknow, Samuel; Kai, Shumpei; Hiraoka, Shuichi; Cookson, Nikki J.; Zysman‐Colman, Eli; Hardie, Michaele J.
Abstract: The racemic ligands (±)‐tris(isonicotinoyl)‐cyclotriguaiacylene (L1), or (±)‐tris(4‐pyridyl‐methyl)‐cyclotriguaiacylene (L2) assemble with racemic (Λ, Δ)‐[Ir(ppy)2 (MeCN)2 ] +, in which ppy=2‐phenylpyridinato, to form [{Ir(ppy)2 }3 (L)2 ] 3+ metallo‐cryptophane cages. The crystal structure of [{Ir(ppy)2 }3 (L1)2 ]⋅3BF4 has MM ‐ΛΛΛ and PP ‐ΔΔΔ isomers, and homochiral self‐sorting occurs in solution, a process accelerated by a chiral guest. Self‐recognition between L1 and L2 within cages does not occur, and cages show very slow ligand exchange. Both cages are phosphorescent, with [{Ir(ppy)2 }3 (L2)2 ] 3+ having enhanced and blue‐shifted emission when compared with [{Ir(ppy)2 }3 (L1)2 ] 3+ . Abstract : Some assembly required ! Homochiral [{Ir(ppy)2 }3 (L)2 ] 3+ metallo‐cages are obtained from the assembly of (Λ, Δ)‐[Ir(ppy)2 (MeCN)2 ] + with racemic cavitand host molecules decorated with pyridyl ligands (L), and ligand‐exchange is observed in solution (ppy=2‐phenylpyridinato). Cages are emissive, and small differences in theL ‐ligands lead to quite distinct emission properties.